The Differences of Pati and Kudus Dialect: Dialectological Studies - Ayu Ratnasari; Indah Arvianti; Didit Kurniadi (Surakarta English and Literature Journal, 2022)
Dialectology is the study of dialects or the study of language variations. Kudus and Pati are two neighbouring towns. Even though the towns are close, there are many different dialects between the two. The objectives of this study are to find out the characteristics and the differences between Pati and Kudus dialect. The research design is descriptive qualitative method and the data collection method to get the data are simak, interview and introspective methods. The results of this study show that there are some differences in both dialects. The dialect variations which occurs in both observation areas are phonological differences which consist of the process of vowel and consonant change, morphological differences with the affixation differences, syntax differences for affirmation, and lexical differences in which the different words have the same meaning. The research gives contribution to the development of local language, especially Javanese related to the Javanese teaching at school, so that it will make the teaching and learning process getting easier in Kudus and Pati. Meanwhile for practical contribution, it completes Javanese standard and Javanese dictionary.